(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nella Rivista “Il Diritto ecclesiastico” SOMMARIO: 1. Le dimissioni da “socio aderente non da fedele”: il caso della sentenza della Corte di Appello di Bari, 28 ottobre 2014 - 2. Rilevanza ed effetti dell’“annuncio” alla comunità - 3. La regola dell’ostracismo - 4. La preminenza dell’autonomia confessionale nella giurisprudenza CEDU: osservazioni critiche - 5. Il bilanciamento tra persona e comunità nella post-modernità. Abstract: Religious Belonging and Ostracism: something new, or rather old, in the dynamics of the religious affiliation The case relating to the resignation as “adherent”, and not as “believer”, to the Christian Congregation of Jehovah’s Witnesses (App. Bari, October 28, 2014), brings out again the problem of the relationship between individual and authorities in the religious confessions. Indeed the procedures followed in order to limit the intra-confessional dissent can bring about an ostracism, biasing the dynamics of the religious affiliation. This paper indicates the novelties of the problem, as pointed out by the sociological studies, in order to accommodate the always necessary balance between the rights of the person and the power to inflict banishments, recognized to the community (autonomy).